SEMANTICS AND PRAGMATICS: UNDERSTANDING THE MEANING AND USE OF LANGUAGE (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article provides an overview of the themes of semantics and pragmatics in linguistics, exploring how they help us understand the meaning and use of language. It highlights the importance of semantics in studying the meaning of words and phrases, including word relationships such as synonyms and antonyms. The article also delves into pragmatics, discussing how language is used to achieve specific goals and how meaning is interpreted based on context.